Маркетинговое обеспечение инновационного развития промышленных предприятий - Ильяшенко, Сергей Николаевич; Ильяшенко, Наталья Сергеевна; Шипулина, Юлия Сергеевна (Київський національний економічний університет ім. Вадима Гетьмана, 2020)
Предложена схема управления выбором мероприятий маркетингового сопровождения различных вариантов коммерциализации инновационной продукции промышленного предприятия, которые выделены по степени охвата этапов инновационного и жизненного цикла продуктовой инновации. Она позволяет укрупнено очертить круг методов и инструментов маркетинга инноваций, которые обеспечивают маркетинговое сопровождение выбранных вариантов коммерциализации.

Describes the variants of the innovation process, distinguished by the degree of coverage of the stages of innovation and life cycle of a new product, and, accordingly, options for commercialization of innovations. Refinements and systematization of problems of marketing of innovations for the selected variants of the innovation process and variants of commercialization of innovations are carried out. The features of the tasks of marketing of innovations peculiarities of the innovation marketing tasks, according to the state of consumer readiness in which the target consumers of the new product are located (actual or potential), are identified.
Marketing innovation development of industrial enterprise
Keywords: маркетинг инноваций; инновационное развитие; промышленные предприятия; marketing innovation; innovation development; industrial enterprises